Tracking the re-emergence of epidemic chikungunya virus in Indonesia - Laras, Kanti; Sukri, Nono C; Larasati, Ria P; Bangs, Michael J; Kosim, Rizal; Djauzi; Wandra, Tony; Master, John; Kosasih, Herman; Hartati, Sri; Beckett, Charmagne; Sedyaningsih, Endang R; et al. (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2005)
Twenty-four distinct outbreaks of probable chikungunya (CHIK) etiology were identified throughout Indonesia from September 2001 to March 2003, after a near 20-year hiatus of epidemic CHIK activity in the country. Thirteen outbreak reports were based on clinical observations alone, and 11 confirmed by serological/virological methods. Detailed epidemiological profiles of two investigated outbreaks in Bogor and Bekasi are presented. Human sera were screened using an ELISA for IgM and IgG anti-CHIK antibodies. Additionally, reverse transcriptase PCR and virus isolation were attempted for virus identification. The mean age of cases was 37 +/- 18 years in Bogor and 33 +/- 20 years in Bekasi. There was no outstanding case-clustering, although outbreak-affected households were observed to be geographically grouped within villages. The attack rates in Bogor and Bekasi were 2.8/1000 and 6.7/1000 inhabitants respectively. Both outbreaks started in the rainy season following increased Aedes aegypti and A. albopictus densities.